Bistetracene Thin Film Polymorphic Control to Unravel the Effect of Molecular Packing on Charge Transport. Issue 9 (26th February 2018) - Burnett, Edmund K.; Ly, Jack; Niazi, Muhammad R.; Zhang, Lei; McCuskey, Samantha R.; Amassian, Aram; Smilgies, Detlef‐M.; Mannsfeld, Stefan C. B.; Briseno, Alejandro L.
Abstract: Polymorphism, the ability for a given material to adopt multiple crystalline packing states, is a powerful approach for investigating how changes in molecular packing influence charge transport within organic semiconductors. In this study, a new "thin film" polymorph of the high‐performance, p‐type small molecule N‐octyldiisopropylsilyl acetylene bistetracene (BT) is isolated and characterized. Structural changes in the BT films are monitored using static and in situ grazing‐incidence X‐ray diffraction. The diffraction data, combined with simulation and crystallographic refinement calculations, show the molecular packing of the "thin film" polymorph transforms from a slipped 1D π‐stacking motif to a highly oriented and crystalline film upon solvent vapor annealing with a 2D brick‐layer π‐stacking arrangement, similar to the so‐called "bulk" structure observed in single crystals. Charge transport is characterized as a function of vapor annealing, grain orientation, and temperature. Demonstrating that mobility increases by three orders of magnitude upon solvent vapor annealing and displays a differing temperature‐dependent mobility behavior. Abstract : A bistetracene thin‐film polymorph is accessed by spin‐coating and the molecular packing is characterized utilizing crystallographic refinement calculations. Solvent vapor annealing converts the film from 1D π‐stacking motif to the bulk‐crystal 2D "brick‐layer" packing. Temperature‐dependent mobility demonstrates a transition from a hopping charge transport mechanism in the thin film polymorph to a lattice‐scattering dominated behavior in the solvent‐annealed film.